Finite element simulation of single crystal and polycrystalline Haynes 230 specimens. (1st June 2017) - Luccarelli, P.G.; Pataky, G.J.; Sehitoglu, H.; Foletti, S.
Abstract: Metallic materials are typically described on the macroscopic scale without consideration that they are an aggregate of grains at the micro scale. Taking this into account, finite element simulations with a crystal plasticity model were used to reproduce the behavior of a Nickel-based superalloy, Haynes 230. The aim of this work was to replicate the local behavior of a real polycrystalline aggregate. The simulation was constructed based on the microstructure of a Haynes 230 sample, obtained via electron backscatter diffraction. Utilizing digital image correlation during the experiment provided the opportunity to directly compare the simulation and experimental results. The present paper includes a description of the numerical model used for the analysis, its application to tensile experiments conducted on single crystal specimens and finally to a polycrystalline specimen. The validation of the results was based on the macro scale behavior of the tensile tests curves and on the local strain accumulation occurring in the grains and along grain boundaries.